Pengaruh Media Diorama Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sosial Tema Masa Kolonial Kelas V SDN Mojokambang 1 Jombang Tahun Ajaran 2024/2025 - Dlurqornain, Ahmad Imam Arif; Susilo, Claudya Zahrani (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The use of diorama media is based on poor student learning outcomes in social studies subjects, namely test scores. The cause of the lack of student learning outcomes is that the media used by teachers are only pictures in books. Teachers should act as a driving force for learning and creative activities in developing learning media, as well as having confidence and skills in using learning media in an impressive way. The aim of this research is to determine the effect of diorema media on student learning outcomes. This research uses the approach used in this research using a quantitative approach, using experimental research. The data collection techniques used include tests and documentation, related to the condition of student learning outcomes in the learning model using diorema media. Results of this research found that 1. Based on the results of the descriptive test above, the mean value from the pretest of student learning outcomes before using diorema media was obtained with a score of 32.00. This shows that the learning outcomes of class V students in social studies subjects with a colonial theme are classified as low, 2. Based on the test results In the descriptive above, the mean value of the posttest on student learning outcomes after using diorema media was obtained with a value of 62.89. This shows that the learning outcomes of class V students in social studies subjects with a colonial theme are classified as moderate, 3. Based on the results of the sample t-test above, the value of sig. (2-tailed) from the preetest and posttest of 0.000 ˂ 0.05. This means that H0 is accepted, so it can be concluded that there is an influence of the use of aroma media on student learning outcomes in social studies lessons with a colonial theme in class V at SDN Mojokembang 1 Jombang.